Ong-bak : Muay Thai warrior - Prachya Pinkaew; Tony Jaa (Thailand : Shamongkol Film International, 2003)
One dark night, a former native of a rural Thai village, has his men steal the head of the town's ONG BAK (Buddha statue) to win favor with ruthless crime boss Khom Tuan. The locals regard the theft as a catastrophe, and seek a champion to retrieve their lost treasure. They find their man in Ting (Tony Jaa), an orphaned youngster raised at the local temple, and schooled by Pra Kru, a kindly monk, in an ancient system of Muay Thai:'Nine Body Weapons'. Ting travels to the mean streets of Bangkok, where he's forced to compete in illegal street fights, taking on both local and foreign opponents to win the head of ONG BAK from the ruthless crime boss.
'He's gonna prove how ultimate Thai martial art is..'
Director of photography, Natawut Kittikun ; editor, Thanat Sunsin.
Tony Jaa, Petchai Wongkamlao, Pumwaree Yodkamol, Rungrawee Borrijindakul, Chetwut Wacharakun.
DVD format, MPEG 2, Region 3, Dolby Digital.
In Thai with optional Chinese, English and Malay subtitles.
Title from title screen.
Keywords: Muay Thai -- Thailand; Martial arts films -- Thailand